2006
DOI: 10.1002/pmic.200500621
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of injured spinal cord tissue proteins using 2-DE and MALDI-TOF MS

Abstract: Spinal cord injury (SCI) induces a progressive pathophysiology affecting cell survival and neurological integrity via complex and evolving molecular cascades whose interrelationships are not fully understood. Acute injury to the spinal cord undergoes sequential pathological change including hemorrhage, edema, axonal and neuronal necrosis, and demyelination. In the present study, we aimed to establish the proteomic profiles and characterization of the total protein expressed in traumatic injured spinal cord tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 32 publications
6
40
0
1
Order By: Relevance
“…It is worth noting that from our 2D PAGE analysis we could only detect HPT in the contusive SCI group but not in the sham group. Moreover the up-regulation of albumin and transferrin was in agreement with a previous study using proteomics analysis of transection-injured spinal cord tissue of rats (34,35). Most importantly, the up-regulation of these proteins was decreased in the aFGF-treated spinal cord tissue after SCI.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…It is worth noting that from our 2D PAGE analysis we could only detect HPT in the contusive SCI group but not in the sham group. Moreover the up-regulation of albumin and transferrin was in agreement with a previous study using proteomics analysis of transection-injured spinal cord tissue of rats (34,35). Most importantly, the up-regulation of these proteins was decreased in the aFGF-treated spinal cord tissue after SCI.…”
Section: Discussionsupporting
confidence: 78%
“…To date, there have been only two reports involving the study of protein profiles of spinal cord injury using a proteomics approach (34,35). However, Ding et al (34) did not dissect the injured spinal segments from the uninjured neighboring tissues, and therefore it is unknown whether the differentially expressed proteins detected in this study were localized in injured spinal region or elsewhere.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Glial fibrillary acidic protein (a class-III intermediate filament protein) was also downregulated at this time point, although a previous study demonstrated glial fibrillary acidic protein upregulation in SCI induced by laminectomy. 4 NEFM, another neurofilament protein, was distributed at six spots with both up-and downregulated patterns. A previous study reported that NEFM expression is influenced strongly in oxidative stress, and estradiol may protect neurons by inducing NEFM expression.…”
Section: Protein Validation By Western Blot and Immunohistochemistrymentioning
confidence: 99%
“…1 Reactive oxidation species have been implicated in this pathogenesis 2 and recent proteomics studies of primary stage SCI have identified some important molecules. 3,4 However, the exact mechanism of ischemia-reperfusion-induced SCI remains unclear and the protein differential level of the second stage of injury is seldom reported. High-throughput proteomics tools promise discovery of molecules involved in the pathological processes of ischemia-reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%